Flavours of resilience: new Chinese immigrant restaurateurs and challenges in shaping the U.S. Chinese restaurant scene (1960s - 1980s) - Wong, Damien Wai Loon (Nanyang Technological University, 2023)
In 1965, the United States of America (U.S.) passed the Immigration and Nationality Act – ushered a historic moment in American history, signalling an increase in immigrants entering the country. The period saw increased Chinese immigration, a drastic contrast to a history marked by exclusion and prejudice, as demonstrated by regulations such as the Chinese Exclusion Act of 1882. While research on Chinese migration to the U.S. between the 1850s to 1920s is extensively covered, my research focuses on the post-1965 timeline. This research explores the varied encounters, obstacles, and roles of Chinese immigrants within the Chinese restaurant industry between the 1960s and the 1980s. This research examines the many historical narratives of Chinese immigrants who arrived in the U.S. after 1965, particularly emphasising the Chinese restaurant business in major urban centres that includes New York and San Francisco. This research also focuses on the commercial tactics used by Chinese restaurateurs after 1965 to handle economic obstacles aggravated by co-ethnic conflicts and political complications.